Vitamin D deficiency in western dwelling South Asian populations: an unrecognised epidemic. Issue 3 (12th August 2020) - Darling, Andrea L.
Abstract : Vitamin D deficiency (25-hydroxyvitamin D; 25(OH)D) is at epidemic proportions in western dwelling South Asian populations, including severe deficiency (<12⋅5 nmol/l) in 27–60% of individuals, depending on season. The paper aimed to review the literature concerning vitamin D concentrations in this population group. Research from the UK and Europe suggests a high prevalence of South Asians with 25(OH)D concentration <25 nmol/l, with most having a 25(OH)D concentration of <50 nmol/l. In Canada, South Asians appear to have a slightly higher 25(OH)D concentration. There are few studies from the United States, South Africa and Australasia. Reasons for vitamin D deficiency include low vitamin D intake, relatively high adiposity, sun exposure avoidance and wearing of a covered dress style for cultural reasons. Possible health effects of deficiency include bone diseases such as rickets and hypocalcaemia in children and osteomalacia in adults. Vitamin D deficiency may also increase the risk of other chronic diseases. Increased fortification of food items relevant to South Asian groups (e.g. chapatti flour), as well as increased use of vitamin D supplements may help reduce this epidemic. Introducing culturally acceptable ways of increasing skin exposure to the sun in South Asian women may also be beneficial but further research is needed to assess the effectiveness of different approaches. There may be a need for a South Asian specific vitamin D dietary intake guideline in western countries. To conclude, vitamin D deficiency is epidemic in South Asians living in western countries and there is a clear need for urgent public health action.